THE USE OF COPPER INDICATOR ELECTRODES IN VOLTAMMETRIC ANALYSIS - L. Yu. Martynov; O. A. Naumova; N. K. Zaytsev; I. Yu. Lovchinovsky (Тонкие химические технологии, 2016)
The review describes the application of solid electrodes based on copper for voltammetric analysis of major classes of organic and inorganic substances over the last fifty years. Despite the fact that there are many reviews of individual solid electrodes this review offers the first comprehensive report on all forms of copper electrodes. The advantages and disadvantages of copper electrodes in comparison with electrodes made of other metals are discussed. Varieties of copper electrodes, their basic physico-chemical properties and some specific characteristics of their surface are described. The electrochemical behavior of copper in aqueous solutions and electrocatalytic mechanisms of transformations of matter on its surface are reported. Examples of the use of electrochemical copper sensors for flow-injection analysis and liquid chromatography are given. Recent trends of the use of copper micro- and nanostructured electrodes in electrochemical analysis are reviewed. The prospects of using copper as a material for the creation of new electrochemical sensors are shown.